Clinical phenotype, laboratory features and genotype of 35 patients with heritable dysfibrinogenaemia. (15th October 2012) - Shapiro, Susan E.; Phillips, Emma; Manning, Richard A.; Morse, Colin V.; Murden, Sherina L.; Laffan, Michael A.; Mumford, Andrew D.
Summary Heritable dysfibrinogenaemia (HD) is a rare qualitative disorder of fibrinogen (FGN). To better describe the clinical, laboratory and genotypic spectrum of HD, we evaluated 35 subjects identified at two UK centres using laboratory criteria. 12/35(34%) subjects with HD experienced bleeding (bleeding score >1 at any site), 3/35(9%) thrombosis and 20/35(57%) were asymptomatic. Amongst subjects with bleeding, symptoms were typically mild, at one anatomical site and seldom occurred after invasive procedures. All subject showed dry clot weight within or above laboratory reference interval (median 3·2 g/l; range 1·9–5·1), reduced Clauss fibrinogen (median 0·52 g/l; range 0·21–1·3), and prolonged thrombin (median 30·7 s; range 21·3–45·7) and reptilase (median 42·0 s; range 20·0–68·0) times. In all subjects, the prothrombin time ratio (PTR), determined by Sysmex CA‐1500 coagulometer and Innovin activator, was abnormal (median 1·42; range 1·22–1·61). The activated partial thromboplastin time ratio and PTR with other coagulometers and activators were comparatively insensitive to HD. All subjects with HD harboured heterozygous candidate nucleotide variations within known hotspots in the FGN genes. The HD variants identified in this cross‐sectional study seldom have significant clinical manifestations and show similar laboratory features irrespective of genotype. Selection of coagulometer and PT activator may markedly affect the detection of new HD cases using coagulation screening tests.